Mapping Solanum chacoense mediated Colorado potato beetle (Leptinotarsa decemlineata) resistance in a self-compatible F2 diploid population - Kaiser, N.; Manrique, N.; DiFonzo, C.; Coombs, J.; Douches, D. (Springer, 2020)
We examined the genetic features underlying leptine glycoalkaloid mediated Colorado potato beetle (Leptinotarsa decemlineata) host plant resistance in a diploid F2 mapping population of 233 individuals derived from Solanum chacoense lines USDA8380-1 and M6. The presence of foliar leptine glycoalkaloids in this population segregated as a single dominant gene and displayed continuous distribution of accumulated quantity in those individuals producing the compound. Using biparental linkage mapping, a major overlapping QTL region with partial dominance effects was identified on chromosome 2 explaining 49.3% and 34.1% of the variance in Colorado potato beetle field resistance and leptine accumulation, respectively. Association of this putative resistance region on chromosome 2 was further studied in an expanded F2 population in a subsequent field season. Loci significantly associated with leptine synthesis colocalized to chromosome 2. Significant correlation between increased leptine content and decreased Colorado potato beetle defoliation suggests a single QTL on chromosome 2. Additionally, a minor QTL with overdominance effects explaining 6.2% associated with Colorado potato beetle resistance donated by susceptible parent M6 was identified on chromosome 7. Bulk segregant whole genome sequencing of the same F2 population detected QTL associated with Colorado potato beetle resistance on chromosomes 2, 4, 6, 7, and 12. Weighted gene co-expression network analysis of parental lines and resistant and susceptible F2 individuals identified a tetratricopeptide repeat containing protein with a putative regulatory function and a previously uncharacterized acetyltransferase within the QTL region on chromosome 2, possibly under the control of a regulatory Tap46 subunit within the minor QTL on chromosome 12.